Application of an Efficient Gene Targeting System Linking Secondary Metabolites to their Biosynthetic Genes in Aspergillus terreus - Guo, Chun-Jun; Knox, Benjamin P; Sanchez, James F; Chiang, Yi-Ming; Bruno, Kenneth S; Wang, Clay C. C (Organic letters, 2013)
Nonribosomal peptides (NRPs) are natural products biosynthesized by NRP synthetases. A kusA-, pyrG- mutant strain of Aspergillus terreus NIH 2624 was developed that greatly facilitated the gene targeting efficiency in this organism. Application of this tool allowed us to link four major types of NRP-related secondary metabolites to their responsible genes in A. terreus. In addition, an NRP affecting melanin synthesis was also identified in this species.